PENGEMBANGAN BAHAN AJAR BERBASIS APLIKASI ANDROID DENGAN SISTEM MIT APP INVENTOR PADA MATERI SIKLUS AKUNTANSI PERUSAHAAN DAGANG KELAS X SMK AKUNTANSI - Ningsih, Eva Mardian; Susilowibowo, Joni (Universitas Islam Negeri Alauddin Makassar, 2021)
The development of technology and information has an important influence on the field of education, one of which is the presence of an online learning system (on the network/online). So that the shock arising from the development of communication technology has triggered teachers or education personnel to be required to be more active, innovative, and creative while creating a learning atmosphere and the design of teaching materials that will be applied in the classroom, especially during the Covid-19 pandemic. This study aims to produce teaching materials based on android applications with the mit app inventor system in the accounting cycle material of trading companies for class X SMK Accounting. This study uses the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Collecting research data using review sheets and expert validation sheets and student response questionnaires. The results of the development research get a very feasible category with a material feasibility score of 83.72%, media feasibility of 84.05%, and language feasibility of 90.95%. The average percentage of all three components of the eligibility of experts is 86.24%. The results of the student response questionnaire showed the results of the feasibility of 98.40%. Thus, teaching materials based on android applications with the mit app inventor system on trading company accounting cycle materials can be declared very suitable for use in the learning process.